Collaborative Governance in the Jogja Berwakaf Movement - Mahmudi Mahmudi; Danang Wahyu Muhammad (Justicia Islamica, 2022)
This research aimed to look into the collaborative governance model proposed by the Jogja Berwakaf Movement in the Special Region of Yogyakarta (DIY). Data mining is based on primary and secondary legal sources linked to waqf governance employing empirical juridical research methodologies and transformational approaches. Meanwhile, a qualitative descriptive model was employed to analyze the data. The study's findings demonstrate that the Jogja Berwakaf Movement's program has successfully mobilized government and private partners in the DIY to collaborate and collaborate to address the community's socioeconomic difficulties. The Jogja Berwakaf Movement has raised awareness of waqf productivity's significance in speeding economic growth, socio-economic empowerment, and poverty alleviation. This movement resulted in a variety of program models, including the collection of innovative waqf through waqf auctions, literacy and education of waqf to the community through the 'Kopi Luwak' and 'Kopi Lawak' events, digitization of waqf integrated with poverty data in Sleman Regency, waqf corner at KUA throughout DIY through integrated waqf application and various other collaboration-based socialization, collection, and distribution programs of waqf. Through this collaborative movement, waqf governance is more optimal and directed, and the multiplayer effect is getting bigger. From the results of this study, apart from contributing to the acceleration of waqf governance in the regions, it can also become a rule model for sustainable waqf governance in Indonesia.